Luminescent electrochromic devices for smart windows of energy-efficient buildings - Fernandes, Mariana (2018)
To address the challenges of the next generation of smart windows for energy-efficient buildings, new electrochromic devices (ECDs) are introduced. These include indium molybdenum oxide (IMO), a conducting oxide transparent in the near-infrared (NIR) region, and a NIR-emitting electrolyte. The novel electrolytes are based on a sol-gel-derived di-urethane cross-linked siloxane-based host structure, including short chains of poly (ε-caprolactone) (PCL(530) (where 530 represents the average molecular weight in g mol−1). This hybrid framework was doped with a combination of either, lithium triflate (LiTrif) and erbium triflate (ErTrif3), or LiTrif and bisaquatris (thenoyltrifluoroacetonate) erbium (III) ([Er(tta)3(H2O)2]). The ECD@LiTrif-[Er(tta)3(H2O)2] device presents a typical Er3+ NIR emission around 1550 nm. The figures of merit of these devices are high cycling stability, good reversibility, and unusually high coloration efficiency (CE = ΔOD/ΔQ, where Q is the inserted/de-inserted charge density). CE values of −8824/+6569 cm2 C−1 and −8243/+5200 cm2 C−1 were achieved at 555 nm on the 400th cycle, for ECD@LiTrif-ErTrif3 and ECD@LiTrif-[Er(tta)3(H2O)2], respectively.